Multi-scenario simulation analysis of cultivated land based on PLUS model—a case study of Haikou, China - Lin, Xiaofu; Fu, Hui (Frontiers in Ecology and Evolution, 2023)
Land-use changes have received increasing attention since the 1990s. Cultivated land is a vital land resource with both natural and economic features. Socioeconomic development profoundly affects the spatiotemporal evolution of cultivated land. In turn, the spatiotemporal change of cultivated land also reflects the socioeconomic development trend. This study took Haikou City, which has the highest degree of urbanization in Hainan Province, as the study area, analyzed the spatiotemporal evolution characteristics of its cultivated land resources during the past 20 years of rapid socioeconomic development, and predicted the future spatiotemporal evolution trends of its cultivated land resources on this basis, to provide scientific reference for the rational use and sustainable development of the cultivated land resources in Haikou. This study applied the single land-use dynamic degree (SLUDD) and land-use transfer matrix to explore the spatiotemporal evolution of cultivated land in Haikou from 2000 to 2020. Introduced the patch-generating land use simulation (PLUS) model to predict the patterns of cultivated land under different development scenarios in 2030. The results showed that: (1) although rapid socioeconomic development has contributed to Haikou’s urbanization rate over the past 20 years, the accompanying expansion of construction land has caused damage to cultivated land resources, especially in urban suburbs. Site conditions, differential land benefits, and urban economic radiation may be potential influencing factors leading to the loss of peri-urban cultivated land; (2) it was verified that the PLUS model applies to the land-use patterns prediction in Haikou; (3) the simulation results of both natural and urban development scenarios not only predicted the continued loss of cultivated land in the original zone but also exposed new sites of cultivated land loss. Although construction land expansion is an inevitable trend, there is still hope that the expansion rate can be controlled, for example, under the cultivated land conservation scenario. The simulation results of the three scenarios have essential reference values for the future maintenance of cultivated land resource security in Haikou.